(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Building is generally of the largest employment businesses in the globe, as well as one of most significant providers of jobs. For years, the industry has been plagued by low production and limited technological advancements. The building sector has lately been more interested in different automation, like 3D printing. printing in architecture has demonstrated to be incredibly promise in regards of automation construction procedures, and it has the capacity to save time, money, and potentially risky people activities, among other things. A lot of research has gone into better understanding present advances, future prospects, and challenges related with large scale usage of 3D printing in construction projects. Since building is an employment business, this study examines the impact of increased 3D printing adoption on the labor market. It has been revealed that 3D printers may reduce the quantity of labor necessary, which might assist to alleviate the labor shortages problem, especially in countries where building is heavily dependent on immigrants. In countries where construction is a big employment and labour is lower expensive, however, 3D printing may not be beneficial. Furthermore, professionals with specific understanding of this novel technique will be required to employ 3D structure manufacturing.